2022
DOI: 10.1002/ctm2.1021
|View full text |Cite
|
Sign up to set email alerts
|

Sweet taste receptor agonists attenuate macrophage IL‐1β expression and eosinophilic inflammation linked to autophagy deficiency in myeloid cells

Abstract: Background Eosinophilic inflammation is a hallmark of refractory chronic rhinosinusitis (CRS) and considered a major therapeutic target. Autophagy deficiency in myeloid cells plays a causal role in eosinophilic CRS (ECRS) via macrophage IL‐1β overproduction, thereby suggesting autophagy regulation as a potential therapeutic modality. Trehalose is a disaccharide sugar with known pro‐autophagy activity and effective in alleviating diverse inflammatory diseases. We sought to investigate the therapeut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 95 publications
0
5
0
Order By: Relevance
“…Saccharin exerts an anti-inflammatory effect by inhibiting iNOS expression in the RAW 264.7 macrophage cell line [52] and reducing IL-1β mRNA expression in the 3T3-L1 adipocyte cell line [53]. Our previous study revealed that saccharin reduces IL-1β production from macrophages via a mechanism dependent on the sweet-taste receptor T1R3 but independent of autophagy and thereby attenuates eosinophilic inflammation in a murine model of ECRS [48]. In diverse inflammatory disorders including psoriasis, the role of autophagy depends on the cell type; therefore, targeting autophagy systemically as a therapeutic modality is challenging [54,55].…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…Saccharin exerts an anti-inflammatory effect by inhibiting iNOS expression in the RAW 264.7 macrophage cell line [52] and reducing IL-1β mRNA expression in the 3T3-L1 adipocyte cell line [53]. Our previous study revealed that saccharin reduces IL-1β production from macrophages via a mechanism dependent on the sweet-taste receptor T1R3 but independent of autophagy and thereby attenuates eosinophilic inflammation in a murine model of ECRS [48]. In diverse inflammatory disorders including psoriasis, the role of autophagy depends on the cell type; therefore, targeting autophagy systemically as a therapeutic modality is challenging [54,55].…”
Section: Discussionmentioning
confidence: 95%
“…Our previous study revealed that artificial sugars, particularly saccharin, exert an anti-inflammatory effect on macrophage IL-1β production in an autophagy-independent manner [48]. Based on this finding, we investigated whether saccharin ameliorates IMQ-induced psoriatic skin inflammation in Atg7 fl/fl ;LysM-Cre mice.…”
Section: Saccharin Suppresses Il-1β Expression and Alleviates Autopha...mentioning
confidence: 94%
“…Moreover, the researchers demonstrated that blockade of the IL-1 receptor could alleviate eosinophilic inflammation, suggesting an IL-1 dependent pathway in eCRS due to autophagy deficiency. In a separate study, Lee et al (2022) discovered that the anti-inflammatory effects of sweet taste receptor (STR) agonists, particularly trehalose, significantly mitigated eosinophilia, and disease pathogenesis in eCRS mice with autophagy deficiency in myeloid cells. Their mechanistic investigation revealed the involvement of T1R3 in reducing macrophage IL-1β production and eosinophilia in CRS, which was supported by genetic manipulation of T1R3 expression in macrophages and treatment with the T1R3 antagonist gurmarin.…”
Section: Autophagy In Cellular Experiments and Animal Modelsmentioning
confidence: 99%
“…Future in vitro experiments using both cell types could shed light on the differences in autophagy levels and their impact on CRS progression. The review focused on eCRS models, leaving room for further exploration of autophagy differences in non-eCRS models ( Choi et al, 2018 ; Lee et al, 2022 ). Non-type 2 inflammation in CRS, represented by LPS, IFN-λ, and HNE-stimulated HNEpCs, often shows autophagy excess involving AMPK-mTOR, JNK–AP-1, and HNE-TRAF6 pathways ( Wang et al, 2017a ; Wang et al, 2017b ; Ye et al, 2019 ).…”
Section: Concluding Remarks and Future Perspectivesmentioning
confidence: 99%
See 1 more Smart Citation